The Impact of Information System Implementation (Simgos) in Health Services (Case Study: Pratama Medisal Clinic, Ambon City) - Kusnadi, Yahdi; Tuankotta, Ramadhani Ahmad (Universitas Mohammad Husni Thamrin, 2025)
The rapid development of information technology has become a major pillar of society due to its ability to provide fast and accurate information. This technology is important in various fields, including health, education, economics, finance, social, political, and environmental. In health, information technology assists services by managing and storing administrative data, patient registration, and other information that supports users of health facilities. The Pratama Medisal Clinic in Ambon City is a health facility that prioritizes efficiency and effectiveness in services. This clinic has implemented an Open Source Generic Management Information System. The study used a quantitative method with simple linear regression analysis, data were collected through interviews, observations, and questionnaires, and used a proportionate stratified random sampling technique. Based on the results of the hypothesis test, the implementation of a web-based information system showed a significant effect on employee performance, with a significance value of 0.001. This leads to the acceptance of the H1 hypothesis, while the t-test results show that the calculated t (7.459) is greater than the t-table (1.812), so H0 is rejected. Statistically, the t-test results show a value less than 0.05 (0.001 < 0.05). From this, it can be concluded that the better the information system in healthcare services at a clinic, the better the employee performance. This encourages each clinic to implement information systems in their daily work to increase efficiency. It is hoped that the Medisal Clinic can continue to improve the Open Source Generic Management Information System in health services.